Recensão: Angela Conrad, 'The Wayward Nun of Amherst: Emily Dickinson and Medieval Mystical Women', New York, Garland, 2000, 164 pp. - Freitas, Marinela Carvalho (Cadernos de Literatura Comparada, 2002)
.